Event Organizer sebagai Peluang Wirausaha - Donny Perdana de Keizer (Humaniora, 2011)
The article discusses business chance in event organizer that could be conducted by anybody. Less employment in this country is not balanced with the amount of college graduates every year, which is getting bigger. Government ability to create new jobs does not give a credible chance for new graduates to work. However, there are still chances in building new jobs by being entrepreneurs in event organizer sector. Event organizer service is a business that gives chances in effective employment for society; especially new college graduates so instead of competing to get jobs, they will create a self-employment and also for others. Beginning business in event organizer is not hard as we thought. In the article, it is attached several tips to begin event organizer business.